Preparation of Apatite-Wollastonite-Phlogopite glass-ceramic composites by powder sintering method - Faeghi-Nia A. (Science of Sintering, 2013)
An Apatite-Wollastonite-Phlogopite glass-ceramic composite, was developed by sintering and crystallization of the powdered glass. The non-isothermal and isothermal sintering kinetics were studied for this glass-ceramic. Hot-stage microscopy (HSM) measurements demonstrated that it is possible to sinter and crystallize this glass-ceramic with 80% relative density. The activation energy of sintering was analyzed using previously reported model of sintering and it was obtained Q=193.83 KjmolK-1. Also it was shown that the microstructure of sample is a function of particle size distribution.